MO852: Predialysis Blood-Pressure Control Based on Antihypertensive Guidelines Should Deteriorate Cardiovascular Prognosis in Patients on Maintenance Dialysis. (3rd May 2022) - Omae, Kiyotsugu; Ogawa, Tetsuya; Kyono, Ai; Nishizawa, Yoko; Hosoda, Yumi; Hirasawa, Eriko; Tosaka, Mai
Abstract: BACKGROUND AND AIMS: Guidelines of KDOQI for dialysis patients on blood-pressure (BP) targets proposed blow 140/90 mmHg at predialysis and < 130/80 mmHg at postdialysis. On the other hand, in dialysis patients, many reports have shown an association between predialysis hypotension and poor prognosis. Moreover, it has been reported that low systolic blood-pressure (SBP) is associated with poor prognosis in non-dialysis patients with heart failure. Therefore, predialysis BP controlled according to KDOQI guideline should worsen survival rate in dialysis patients, especially with any cardiac disease. This time, we investigated the difference on cardiovascular survival-rate between the group complied with KDOQI guidelines and the group complied with them for diastolic blood-pressure alone, by using Yoshikawa clinic dialysis-database (YCD). METHOD: A total of 455 dialysis patients (264 males and 176 females) registered in YCD enrolled in this study from April 2006 on. From these patients, we extracted two groups, group G, strictly lowering on systolic and diastolic blood-pressure and group D, lowering on diastolic blood-pressure (DBP) alone, in accordance with antihypertensive guidelines. According to calculated propensity score on group G, patients were extracted by 1: 1 matching from each group. Their survival analysis was estimated by Kaplan–Meier method, and a log-rank test was used to examine the differences between the cardiovascular survival curves. The prognostic factors for cardiovascular mortality were extracted from background factors, including blood-pressure level, using Cox regression model. RESULTS: In 455 patients, mean predialysis SBP and DBP were 143.3 mmHg and 73.1 mmHg, respectively. 141 patients were extracted as group G and 219 were as group D. According to calculated propensity-score, 116 pairs (group Gp and Dp) were extracted from group G and D. There was no significant difference in matching covariates except predialysis blood-pressure between the two groups. During mean-observational period of 5.8 years, 111 patients died, among that 59 were cardiovascular death (CVD). The survival curve on cardiovascular mortality in the group Gp showed significantly poor prognosis. In multivariate analysis of Cox proportional hazard model, SBP < 140 mmHg was extracted as a prognostic factor for CVD, and the hazard ratio was 1.892. On the other hand, in group Dp, non-cardiovascular prognosis was poor, especially in those < 70 years old. CONCLUSION: Blood-pressure control in maintenance dialysis-patients based on current antihypertensive guidelines (KDOQI) should worsen their cardiovascular prognosis. Therefore, it is necessary to set SBP control for each case. This study is a cohort study with a single institution, and a prospective study with multiple institutions will be needed in the future.